Factors Influencing Tourist’s Decision-Making in Consuming Local Culinary in Yogyakarta - Agusteine, Audia; Yunianti, Nining; Syamsu, Moch. Nur (HK-Publishing, 2025)
Abstract This study examined the factors influencing tourists’ decision-making in consuming local culinary in the Special Region of Yogyakarta, focusing on gudeg as the city’s culinary icon. Based on the Consumption Value Theory, the research analyzed the effects of Tourist’s Local Food Consumption Value (TLFCV), Tourist’s Local Food Experiential Value (TLFEV), Attitude Toward Local Food (ATLF), and Food Destination Image (FDI) on Behavioral Intention (BIs). A survey of 220 tourists who had previously consumed gudeg was conducted using purposive sampling, and the data were analyzed with SEM-PLS. Results showed that TLFCV and TLFEV significantly influenced ATLF, while TLFEV also affected FDI. ATLF had a significant positive effect on BIs, whereas TLFCV did not significantly affect FDI, and FDI did not significantly affect BIs. These findings emphasize the importance of consumption and experiential values in strengthening tourists’ behavioral intention in consuming local culinary. Keywords: consumption value, culinary experience, behavioral intention.